Final Oral/Poster Number 2019
DOI: 10.1136/bmjpo-2019-rcpch-sahm.26
|View full text |Cite
|
Sign up to set email alerts
|

P20 The relationship between a trusted adult and adolescent health and education outcomes: A systematic review

Abstract: Aim The epidemiological transition has resulted in a large population of adolescents in Malaysia, whose health burden is poorly described. We set out to provide a comprehensive profile of health in Malaysian adolescents to illustrate important targets for health actions. Methods A conceptual framework for reporting health and wellbeing of Malaysian adolescents was defined to measure health outcomes, health risks and sociocultural determinants. Data from the Global Burden of Disease 2017 study were used to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In line with previous research (Miller-Lewis et al, 2014; Patalay et al, 2019; Van Ryzin et al, 2009; Wang et al, 2013), a higher level of school belonging was associated with better mental health, as was positive student-teacher relationships. The positive impact of teachers in the current study supports recent policy work in Scotland regarding the protective effect of “one trusted adult” for adolescent mental health (Whitehead et al, 2019). Further, perceptions of greater exam pressure in school were associated with worse mental health, while those who perceived their school to be inclusive reported better mental health.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous research (Miller-Lewis et al, 2014; Patalay et al, 2019; Van Ryzin et al, 2009; Wang et al, 2013), a higher level of school belonging was associated with better mental health, as was positive student-teacher relationships. The positive impact of teachers in the current study supports recent policy work in Scotland regarding the protective effect of “one trusted adult” for adolescent mental health (Whitehead et al, 2019). Further, perceptions of greater exam pressure in school were associated with worse mental health, while those who perceived their school to be inclusive reported better mental health.…”
Section: Discussionsupporting
confidence: 85%
“…For example, the systematic review of out-of-school youth development interventions (Ciocanel, Power, Eriksen, & Gillings, 2017), reported benefits relating to educational achievement and psychological adjustment, but not to problem behaviour or sexual risk behaviour. Such variations may be down to limitations within individual study tools or the study methods utilised (Whitehead et al, 2019), but are nevertheless important to note. Details of outcome areas that will be measured as part of, for example, intervention evaluation, can be itemised in section 6 of the taxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the review are reported elsewhere (Whitehead, Pringle, Scott, Milne, & McAteer, 2019). In brief, the review concluded that it is often difficult to specify the unique impact of the trusted adult role on adolescent health and/or education outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were then asked who should receive such alerts. We probed about emergency services, which the Facebook suicide intervention alerts, and trusted adults (parents or guardians and school staff or teachers) frequently identified in prior literature [ 44 , 45 ]. Participants were also probed about why they endorsed or opposed these alert recipients.…”
Section: Methodsmentioning
confidence: 99%